Optimization of Quantum-Dot Molecular Beam Epitaxy for Broad Spectral Bandwidth Devices - M. A. Majid; M. Hugues; S. Vézian; D. T. D. Childs; R. A. Hogg (IEEE Photonics Journal, 2012)
The optimization of the key growth parameters for broad spectral bandwidth devices based on quantum dots is reported. A combination of atomic force microscopy, photoluminescence of test samples, and optoelectronic characterization of superluminescent diodes (SLDs) is used to optimize the growth conditions to obtain high-quality devices with large spectral bandwidth, radiative efficiency (due to a reduced defective-dot density), and thus output power. The defective-dot density is highlighted as being responsible for the degradation of device performance. An SLD device with 160 nm of bandwidth centered at 1230 nm is demonstrated.